(untitled) (Heródoto: Revista do Grupo de Estudos e Pesquisas sobre a Antiguidade Clássica e suas Conexões Afro-asiáticas, 2019)
The new dossier of Revista Heródoto, titled “Cities And Peripheral Areas In The Ancient Word” considers the importance of understanding in parallel the ancient city and the contemporary city we live in. The dossier’s contributions point out the co-dependency of these two cities and the need to reflect on their interpreters and their complex connections with the “world around”.